Temperature dependence of TDDB at high frequency in 28FDSOI. (September 2019) - Arabi, M.; Federspiel, X.; Cacho, F.; Rafik, M.; Nguyen, A.-P.; Garros, X.; Ghibaudo, G.
Abstract: Time Dependent Dielectric Breakdown (TDDB) experiments are performed in the GHz frequency range on a dedicated test structure to mimic operating conditions. It is shown that TDDB device lifetime can be significantly improved at high frequency in the temperature range from −40 °C to 200 °C. In addition, no effect on voltage acceleration is measured between DC and AC stress modes. This result has strong implications for logic circuit lifetime estimation over extended voltage and temperature ranges and gives new insights on the mechanism responsible for AC TDDB effects.